FROM PUNISHMENT TO RECOVERY: OPTIMIZING RESTITUTION IN JUDICIAL DECISIONS ON SEXUAL VIOLENCE CASES - Jea Meysa Maharani Riyadi Putri; Rd. Muhammad Ikhsan; Arya Mandala (Faculty of Law Sriwijaya University, 2026)
Sexual violence is a human rights violation that causes physical, psychological, social, and economic harm to victims. In Indonesian criminal law, victim recovery is an essential aspect, one of which is realized through restitution as regulated in Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence. However, its implementation in judicial practice remains inconsistent. This study aims to analyze the position of restitution in judges’ considerations and assess its function as an instrument for restoring victims’ rights. Using normative legal research with statutory and case approaches, the study finds that restitution is often applied inconsistently and tends to depend on judges’ individual considerations. It is frequently limited to measurable material losses or omitted entirely, resulting in suboptimal victim recovery. This indicates that the victim recovery paradigm has not been fully implemented in criminal justice practice. Therefore, restitution needs to be reoriented as an integral component in adjudicating sexual violence cases to align with the principle of victim protection.